2021
DOI: 10.3390/biology10070638
|View full text |Cite
|
Sign up to set email alerts
|

Protein Model and Function Analysis in Quorum-Sensing Pathway of Vibrio qinghaiensis sp.-Q67

Abstract: Bioluminescent bacteria are mainly found in marine habitats. Vibrio qinghaiensis sp.-Q67 (Q67), a nonpathogenic freshwater bacterium, has been a focus due to its wide use in the monitoring of environmental pollution and the assessment of toxicity. However, the lack of available crystal structures limits the elucidation of the structures of the functional proteins of the quorum-sensing (QS) system that regulates bacterial luminescence in Q67. In this study, 19 functional proteins were built through monomer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 98 publications
(167 reference statements)
0
4
0
Order By: Relevance
“…Molecular docking was then performed using AutoDock Vina to predict the binding modes and affinity of three components [BDE-99, T3, and all-trans retinoic acid (RA)] with THRβ with the settings as previously described. 38 Statistical Analysis. All the data were presented as the mean ± standard error of the mean (SEM).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular docking was then performed using AutoDock Vina to predict the binding modes and affinity of three components [BDE-99, T3, and all-trans retinoic acid (RA)] with THRβ with the settings as previously described. 38 Statistical Analysis. All the data were presented as the mean ± standard error of the mean (SEM).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Based on the NCBI reference sequence (NP_571415.1), homology modeling of THRβ [Danio rerio] was constructed and optimized using the online Swiss modeler server (). Molecular docking was then performed using AutoDock Vina to predict the binding modes and affinity of three components [BDE-99, T3, and all- trans retinoic acid (RA)] with THRβ with the settings as previously described …”
Section: Materials and Methodsmentioning
confidence: 99%
“…This standard is applicable to the detection of acute toxicity in industrial wastewater, wastewater receiving water bodies, and soluble chemicals under experimental conditions. There is no standard that uses Vibrio qinghaiensis, but Vibrio qinghaiensis shows a great advantage in testing as freshwater bacteria [38]. The three luminescent bacteria are applied in different conditions [39][40][41], as shown in Table 1.…”
Section: The Application Of a Traditional Luminescent Bacteria Bioass...mentioning
confidence: 99%
“…Compared with the well-characterized QS systems in V. fischeri and V. harveyi, few studies have shown firm conclusions about whether the luminescence of T3 and Q67 are controlled by QS systems. Based on protein modeling and function analysis on the Q67 strain, Wang et al constructed 18 monomer models for functional proteins potentially involved in QS and bioluminescence to explore how the QS system controlled bioluminescence [12]. However, no clear evidence about the mechanism of bioluminescence in the T3 and Q67 strains has been determined experimentally.…”
Section: Introductionmentioning
confidence: 99%